RANCANG BANGUN ALAT PEREKAM DATA LIKUIFAKSI BERBASIS ARDUINO NANO - Rizana Fauzi; Aidynal Mustari (Foristek, 2019)
Central Sulawesi, precisely in the city of Palu, is one of the areas that frequently occurs in earthquakes and has high seismicity. The regional geology of the Palu area and its surroundings is dominated by quarterly deposits consisting of fluivatil and alluvium deposits. These natural conditions have several potentials that are detrimental, including the potential for liquidity. (Widyaningrum, 2012). Liquidation is an event that occurs when a soil becomes saturated or loses its ability to support the mass above it because the land changes form into heavy water or becomes liquid. Lack of further knowledge about the faction by the surrounding community causes a lack of vigilance in dealing with the faction. The things that people need to know about potentially liquefaction soils are data on soil moisture, changes in underground temperature, and vibrations that are felt underground when earthquakes occur shortly after liquefaction using a device in the form of an arduino nano-based data recorder. The Design of Arduino Nano Based Likuefaction Data Recording Tool can be used to record and record data on lycufaction disaster events. And is used to make it easier to analyze the potential occurrence of liquefaction in certain regions by utilizing the sensor to measure soil temperature, soil moisture, and vibrations that occur in the soil.